2008
DOI: 10.1183/09031936.00118807
|View full text |Cite
|
Sign up to set email alerts
|

Lung hyperinflation: foe or friend?

Abstract: Breath-hold divers employ glossopharyngeal insufflation (GI) in order to prevent the lungs from compressing at great depth and to increase intrapulmonary oxygen stores, thus increasing breath-hold time.The presented case study shows the physiological data and dynamic magnetic resonance imaging (dMRI) findings of acute hyperinflation, deliberately induced by GI, in a breath-hold diver and discusses the current state of knowledge regarding the associated hazards of this unique competitive sport.Static and dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…Indeed, maximal expiratory and inspiratory pressure did not change after any form of training (Nygren-Bonnier et al 2007b;Tetzlaff et al 2008). This was expected, as the GI maneuvers were aimed at stretching the chest wall alone (Eichinger et al 2008;Nygren-Bonnier et al 2007a, b). GI increases thoracic circumference.…”
Section: Pulmonary Volumesmentioning
confidence: 71%
See 1 more Smart Citation
“…Indeed, maximal expiratory and inspiratory pressure did not change after any form of training (Nygren-Bonnier et al 2007b;Tetzlaff et al 2008). This was expected, as the GI maneuvers were aimed at stretching the chest wall alone (Eichinger et al 2008;Nygren-Bonnier et al 2007a, b). GI increases thoracic circumference.…”
Section: Pulmonary Volumesmentioning
confidence: 71%
“…BHDs able to insufflate large volumes thus expand the chest significantly, giving them a barrel chest appearance. It is possible that they have increased joint mobility and stretch their respiratory muscles so they can increase the chest volume to whatever is anatomically possible (Eichinger et al 2008;Whittaker and Irvin 2007). …”
Section: Pulmonary Volumesmentioning
confidence: 98%
“…The consistency of change is reassuring. A previous case report, based on dynamic magnetic resonance imaging, suggested that there was a symmetrical expansion in the thorax [10]. A second case report also demonstrated cardiac and vascular mediastinum configurational changes [9].…”
Section: Discussionmentioning
confidence: 84%
“…While some of this increase could be from displacement of structures within the thorax (heart, vessels or oesophagus) most of the increase may be related to the change in the configuration of the chest wall and diaphragm. Individual case reports on breath-hold divers have described pulmonary hyperinflation with cardiac compression, aortic stretch and reduction in blood flow using magnetic resonance imaging [9,10].…”
mentioning
confidence: 99%
“…BH divers employ glossopharyngeal mus cle contractions (= glossopharyngeal pistoning; buccal pumping; lung packing) to increase the volume of air in the lungs above TLC [35]. They thereby increase the volume of gas available for pressure equalization during descent [36, 37] and enhance the amount of oxygen available in the lungs [38].…”
Section: Breathing Techniquesmentioning
confidence: 99%